The philosophy of Virginia Woolf - Hussey, Mark Francis (1982)
Following an Introduction which explains how "philosophy" is intended, Chapter 1 describes a scale of characters' 'at-homeness' in the body. VW’s awareness of the body's role is seen as preliminary to her concept of identity.